Electrochemical Detection of Cadmium Using a Bismuth Film Deposited on a Brass Electrode - Milan B. Radovanović; Marija B. Petrović Mihajlović; Ana T. Simonović; Žaklina Tasić; Milan M. Antonijević (Sensors)
Cadmium is one of the most dangerous pollutants found in the environment, where it exists mainly due to human activities. High cadmium concentrations can cause serious problems, which is why the detection and determination of Cd is one of the most important tasks. Electroanalytical methods provide rapid and accurate results in the detection of cadmium in various solutions. In this study, the possibility of using a bismuth film electrode deposited on a brass surface and electroanalytical techniques for the detection of cadmium is investigated. The bismuth film was deposited on the surface of the brass electrode using a chronoamperometric technique. Cyclic voltammetry and electrochemical impedance spectroscopy were used to characterize the synthesized bismuth film electrode. The current peaks obtained by anodic square-wave stripping voltammetry under optimized conditions showed a linear relationship in the investigated concentration range of cadmium. The study of the interference of different cations (Cr3+, Mn2+, Zn2+, Ca2+, K+, Mg2+ and Na+) showed that the tested cations have no influence on the determination of Cd2+ ions in the investigated solution. This finding provides a good opportunity for the use of the synthesized electrode in real samples.